The Effect of International Exchange Programs on Improving The Accreditation of Higher Education : Study analysis at Institute Informatics and Business Darmajaya - Betty Magdalena; Suhailah Sideh; Polina Kurtenkova; Mujuni Kenneth (Proceeding International Conference on Information Technology and Business, 2019)
Study abroad at one of the partner universities of educational institution is important. A student exchange program is a program in which students can study in other countries include not only study abroad, but also various international trips, language courses and summer camps, which are aimed at gaining new knowledge in any field, as well as the practice of a foreign language. The methodology used in this study is a qualitative research that uses descriptive analytic method, which is a method that is not only limited to data collection, but includes data analysis and interpretation. Darmajaya is a private Institute that provide some international programs for students and stuff who want to go abroad. And by these programs the institute has increase accreditation B in 2019 year cause of it can achieve campus quality.Keywords: exchange programs, internation programs, descriptive analytic method, accreditation,high education, IIB darmajaya.